2011
DOI: 10.1155/2011/219350
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin, Plasminogen Activator Inhibitor Type 1 (PAI-1) And Uterine Artery Doppler Velocimetry as Markers of Preeclampsia

Abstract: Objective: The purpose of this study was to examine plasma levels of fibronectin and plasminogen inhibitor type 1 (PAI-1), and alterations in uterine artery (UtA) waveforms throughout normotensive and preeclamptic pregnancies and to analyze its predictive value for the detection of preeclampsia within the second trimester of pregnancy.Material and methods: Blood samples were collected from 102 healthy, nulliparous women between the 24th and 26th gestational week. Preeclampsia developed in 13 patients; 89 normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…Maternal plasma fibronectin levels of patients with preeclampsia were significantly higher than those of healthy pregnant women [77] . Significant elevations in fibronectin levels with an extra type Ⅲ domain occurred in the first trimester before clinical evidence of preeclampsia.…”
Section: Fibronectinmentioning
confidence: 70%
“…Maternal plasma fibronectin levels of patients with preeclampsia were significantly higher than those of healthy pregnant women [77] . Significant elevations in fibronectin levels with an extra type Ⅲ domain occurred in the first trimester before clinical evidence of preeclampsia.…”
Section: Fibronectinmentioning
confidence: 70%
“…Although markers of systemic inflammation [79,80] and endothelial dysfunction [81][82][83][84][85][86][87][88] in maternal blood have been associated with preeclampsia, their prognostic performance for the identification of patients with preeclampsia prior to diagnosis has been disappointing [79][80][81]83,[89][90][91]. This indicates that either inflammation occurs late (even during the subclinical phase of the disease), or that the current methods available to detect intravascular inflammation are not sensitive enough.…”
Section: Introductionmentioning
confidence: 99%
“…Several other research groups reported that abnormal fibronectin [13,15,[27][28][29] and PAI-2 levels [14,[30][31][32] precede the onset of a PS, presumably from 20 weeks pregnancy onward [13-15, 29, 30, 32] . One study measured fibronectin at 13 weeks, but the authors only performed a trend analysis based on 3 consecutive measurements in the first, second and third trimester [16] .…”
Section: Discussionmentioning
confidence: 99%
“…PAI-2 accelerates the conversion of plasminogen into plasmin, which in turn degrades a blood clot [11] . Increased fibronectin and decreased PAI-2 levels precede PE onset as early as at 20 weeks pregnancy [12][13][14][15] . Whether these abnormal peripheral levels also prevail earlier in pregnancy in women who later develop PE is unclear.…”
Section: Introductionmentioning
confidence: 99%